Factors Associated with the Utilization of Tetanus Toxoid Immunization Services among Pregnant Women in Oepoi Health Center, Kupang, East Nusa Tenggara - Chintya Leba Leo; Masrida Sinaga; R. Pasifikus Christa Wijaya (Journal of Health Promotion and Behavior, 2023)
Background: The tetanus toxoid (TT) immunization program is a process of building immunity as an effort to prevent tetanus infection. TT immunization is important to form tetanus antibodies that will prevent neonatal tetanus. The coverage of TT immunization in Oepoi Community Health Center Working Area in 2020 is classified as very low, which was only 37.06%. The low coverage of TT Immunization indicated a lack of utilization of immunization services by pregnant women. This study aimed to determine the factors associated with the utilization of Tetanus Toxoid immunization services for pregnant women in the working area of the Oepoi Health Center.Subjects and Method: This cross-sectional study was conducted in the working area of the Oepoi Health Center, Kupang, East Nusa Tenggara from March to October 2022. A total of 46 third trimester pregnant women were selected by simple random sampling. The dependent variable was the TT immunization service. The independent variables were knowledge, the role of health workers, husband's support, and parity. Data was collected by using a questionnaire and analyzed by using the chi-square test.Results: There is a relationship between knowledge (OR= 48.00; 95%CI= 7.84 to 293.71; p<0.001), the role of health workers (OR= 22.16; 95%CI= 2.57 to 190.99; p<0.001) husband’s support (OR=10.85; 95%CI= 2.68 to 43.89; p<0.001), parity (OR= 3.73; 95%CI= 1.08 to 12.90; p= 0.033) and the utilization of the TT immunization service in the Oepoi Health Center working area.Conclusion: Knowledge, the role of health workers, husband's support, parity are related with the utilization of TT immunization services in the working area of the Oepoi Health Center.Keywords: immunization, tetanus toxoid, pregnant women.Correspondence:Chintya Leba Leo. Faculty of Public Health, Universitas Nusa Cendana Kupang. Jl. Adisucipto Number 1 Penfui Kotak Pos 104 Kupang 85001, East Nusa Tenggara. Email: chintyalebaleo@gmail.com. Mobile: +62 813-3855-7740.Journal of Health Promotion and Behavior (2023), 08(01): 58-64DOi: https://doi.org/10.26911/thejhpb.2023.08.01.08